The Shaded Dome™: A Smart, Cool & Adaptable Facility for Sport Venues. (2016) - Torsing, Rob; Oosterman, Kay; Bakker, Jack; Hinssen, Mart; Bosveld, Inge; Huijsmans, Thijs
Abstract: Sports are an integral part of human life and their practice is a common pleasure among people all over the world. Once nature does not provide the required climate conditions for that to happen, humans can take action. Based on that concept, a consortium of three Dutch companies (Zwarts & Jansma Architects, Royal HaskoningDHV, and Polyned) presents a sharp, cool and innovative idea that can facilitate sport's industry in desert-covered areas; the Shaded Dome™. The Shaded Dome™ is a semi-permanent facility, comprised of an air-supported dome excluding any internal supports. A very light and highly resistant outer fabric tent (the Shade) covers it, transforming it into an astonishing state-of-the-art building. A grid of cavity struts links the two layers, creating a peripheral structural system that supports the whole structure. A pleasant internal microclimate is enabled by a constant natural airflow between the dome and the shade together with the use of a custom made combination of several membrane materials. This passive design element provides protection from extreme climatological conditions like solar radiation, wind, high air temperature, humidity and precipitation. The first real-scale models are already under development and the results are extremely encouraging. The current tests show an almost 20 o C temperature decline between the dome's skins, reducing consequently the need for high demanding cooling systems. Next to that the Shaded Dome™ requires limited transport volume, and can be constructed and dismantled in a matter of days. Thus, the preponderant fabrication plan promotes the sources' economy, the efficient materials' use, the reusability of the product and the self-support of its energy needs, highlighting that way a new concept on the asset management of future sport infrastructure. Moving into an era where the need for dynamic constructions is becoming more and more intense, the Shaded Dome™ can constitute an easy to build, quick and fit-for-purpose solution which can efficiently meet any sport infrastructure requirements.